Cloning and expression of the Glomerella cingulata cutinase recombinant gene in the yeast, Pichia pastoris - Lias, Norhatiah Md.; Bakar, Farah Diba Abu; Zamrod, Zulkeflie; Othman, Roohaida; Murad, Abdul Munir Abdul; Nathan, Sheila; Mahadi, Nor Muhammad (Penerbit Universiti Sains Malaysia, 2004)
Glomerella cingulata (anamorph. Colletotrichum gloeosporioides) is a phytophatogenic fungus produces cutinase enzyme causing anthracnose disease of a wide range of plants in the tropics and subtropics. Cutinases are hydrolytic enzymes that are able to hydrolyse ester bonds in the cutin polymer of higher plants which is a polyester composed of hydroxyl and epoxy fatty acids.